Effects Of Money Devaluation On Macroeconomic Indicators Of Developing Countries: Evidence From Pakistan. - Hussain, Javed; Hussain, Nazar; Rehman, Mujeeb Ur; Saqib, Ghulam; Phulpoto, Kamran (The journal of contemporary issues in business and government, 2021)
Pakistan economy is experiencing a biggest trade deficit of history amounting $2.683 billion, hyperinflation, highest rate of unemployment, negative growth rate ticking around -0.2% to -0.4% and US dollar hanging around Rs.160.36. Governments within any state or country are entitled to make most important decisions to run the day to day affairs which affects the lives of people.The policy of currency devaluation exchange rate has been adopted by many countries to shift patterns spending to achieve high levels of production of exportable goods. However along with increasing demand of exportable goods money devaluation has the tendencies of improving trade bills, balancing trade deficits as well but with certain implications. What these implications are and how these effect macroeconomic indicators discussed in this paper. Two variables (Money Devaluation independent variable and Macroeconomic indicators dependent variables) are incorporated to study the cause and effect of the two. Different statistical tools like, Reliability statistics, Regression analysis (ANOVA & Model Summary), Coeffecients and Correlation analysis have been to statistically prove the validity of survey study and it’s generalized acceptability.